Red Hat Linux Fedora for Dummies - Jon 'maddog' Hall ; Paul G. Sery (Mc Graw Hill, 2004)
Red Hat has merged its flagship Red Hat Linux product with the Fedore Project to create the Fedora Core distribution. This handy guide helps you work with Fedora. It walks you through installing and configuring the operating system, getting online, buliding a firewall, using Windows applications with Wine, tuning in to streaming multimedia with MPlayer, and even creating your town secure, private network.